Implementation of Sustainable Development by Cities and Businesses in Poland. Evolution of the Approach - Jastrzębska, Ewa; Legutko-Kobus, Paulina (Studia Ecologiae et Bioethicae, 2022)
Adoption of the UN Sustainable Development Goals (SDG) in 2015 put the theoretical concept of sustainable development (SD) into practice. The goals kindled a vivid interest among Poland-based companies, too, especially large enterprises, which took them to the next level, and embedded them in their corporate strategies. Truth be told, Polish local governments started to implement SD much earlier, namely through Local Agendas 21 after the Second Earth Summit in Rio de Janeiro in 1992. The year 2015 was a pivotal moment for the development of the SD concept. Yet, in the opinion of many experts, 2020 was a major test for SDGs as the COVID-19 pandemic was exerting an adverse impact on the progress in their achievement. The study attempts to assess the approach of SD pioneers in Poland, both cities and companies, to the implementation of the concept in the first year of the pandemic. The text provides a critical analysis of the literature on the subject, web research, and authors’ empirical studies conducted among those cities and businesses in Poland that are considered the leading SD implementers. The conducted research demonstrated that most of these leaders (both cities and businesses) are acquainted with both SD and SDGs. In the period covered by analysis, there was a major growth in SD institutionalization. Both business and city representatives understand SD primarily in accordance with the definition framed in Agenda 2030. A stable majority of the surveyed cities and businesses believe that their approach to SD implementation has changed since the announcement of SDGs in 2015. The COVID-19 pandemic has not halted the implementation of SDGs, although in some cases, it has forced the surveyed implementers to revise their modus operandi.